O marxismo e o problema da escolha moral - Sobreira Filho, Enoque Feitosa (2010)
The aim of this thesis is to analyze the question of moral choice from a critical view of Marxism. The originality of Marx’s thinking is to criticize the idealist philosophies. This current considers it is impossible to understand the established moral values in society or the process of its establishment, without first understanding the environment and the conflicts of that society. Thus, it isn't the thesisproblem of discussing the moral argument as an ontological given, prefixed and closed, but placing the moral and human interests as facts entered in the history and not outside it. According to founders of Marxism, if the human being is the result of conditions, it is, therefore, to make them [these conditions] human.